Assessing the Moral Credentials of the Next Generation of Accountants - Umaru Zubairu; Olalekan Sakariyau; Chetubo Dauda; Isah Paiko (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2016)
Abstract This study assessed the progress of Malaysian universities in producing morally upright accountants by evaluating the moral competencies of the third-year accounting students enrolled at the Universiti Sains Islam Malaysia (USIM). An instrument was developed through a collaboration with Islamic accounting scholars; 79 third-year students were surveyed. The survey revealed that the current crop of the third-year accounting students were not morally competent enough to deal with the inevitable moral dilemmas they would face in the work place. The implication of this result is that USIM’s accounting department has to re-examine its current curriculum as to its ethics coverage. Abstrak Penelitian ini bertujuan untuk menilai perkembangan universitas-universitas di Malaysia dalam hal menghasilkan para akuntan yang jujur. Penelitian ini dilakukan dengan langkah mengevaluasi kompetensi moral mahasiswa akuntansi tahun ketiga di Universiti Sains Islam Malaysia (USIM). Instrumen yang digunakan adalah survey, yang dikembangkan melalui kolaborasi para cendekiawan muslim dengan mensurvey 79 mahasiswa tahun ketiga. Hasil survey menunjukkan bahwa para siswa tahun ketiga akuntansi pada zaman sekarang ini belum memiliki kompetensi moral dalam hal dilemma moral pada bidang pekerjaan mereka. Implikasi penelitian ini adalah berupa saran untuk jurusan akuntansi USIM untuk menguji kembali kurikulum mereka yang berkenaan dengan etika dan moral. How to Cite : Zubairu, U. Sakariyau, O. Dauda, C. Paiko, I. (2016). Assessing the Moral Credentials of the Next Generation of Accountants. TARBIYA: Journal of Education in Muslim Society, 3(2), 168-185. doi:10.15408/tjems.v3i2.4166. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i2.4166